2017
DOI: 10.1093/ehjci/jex223
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale assessment of aortic stenosis: facing the next cardiac epidemic?

Abstract: Burden of AS is higher than previously assumed. Degenerative aetiology is the main cause of AS. Most of the patients are elder with high prevalence of significant co-existing valvular disease. LFLG severe AS is present in an important proportion of patients, showing high grade of left ventricle remodelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 31 publications
0
14
1
Order By: Relevance
“… 17 Similar findings were achieved in a systematic large-scale screening in ~30 000 patients with conventional 2D echocardiography on referral to hospital (7.2%). 18 Although both studies showed a higher AS prevalence than our study, they used full-time sonographers using fully equipped echocardiography machines, while our study used full-time primary care physicians using target 2D scanning alone. Whole population screening using formal echocardiography in those aged >65 years is unlikely as, although the test is relatively cheap, there is a shortage of the required highly skilled accredited sonographers in the UK.…”
Section: Discussioncontrasting
confidence: 52%
“… 17 Similar findings were achieved in a systematic large-scale screening in ~30 000 patients with conventional 2D echocardiography on referral to hospital (7.2%). 18 Although both studies showed a higher AS prevalence than our study, they used full-time sonographers using fully equipped echocardiography machines, while our study used full-time primary care physicians using target 2D scanning alone. Whole population screening using formal echocardiography in those aged >65 years is unlikely as, although the test is relatively cheap, there is a shortage of the required highly skilled accredited sonographers in the UK.…”
Section: Discussioncontrasting
confidence: 52%
“…The incidence of degenerative aortic stenosis (DAS) increases with age, and the coincidence of elderly age, severe DAS, cardiovascular comorbidities, e.g. hypertension, atherosclerosis, arrhythmias, diabetes is commonplace [1][2][3][4]. DAS, is not only a valvular disease, but stenosis leads to extra valvular cardiac complications such as left ventricular hypertrophy, remodeling, fibrosis and myocardial dysfunction [5].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] For years, it has been suggested that classical cardiovascular risk factors such as diabetes, hyperlipidemia, arterial hypertension, smoking, and familial predisposition promote the pathogenesis of calcific aortic valve stenosis. 5,6 In addition to a disturbed calcium metabolism and immunological influences, 7 in particular subacute or acute endocarditis is responsible for the development of sVHD. 8 In 2004 Cohen and colleagues 9 confirmed a link between subclinical bacterial endocarditis and calcification of the aortic valve in an animal model.…”
Section: Perspectivementioning
confidence: 99%